Erect bifoliate species of Microporella (Bryozoa, Cheilostomata), fossil and modern - Di Martino, Emanuela; Taylor, Paul D.; Gordon, Dennis P. (European Journal of Taxonomy, 2020)
Microporella Hincks, 1877 is one of the most diverse genera of cheilostome bryozoans, containing more than 150 named species. Distributed globally since the early Miocene, the majority of species of Microporella have sheet-like colonies encrusting hard and / or ephemeral substrates, while a limited number of species have erect bifoliate colonies starting from an encrusting base. Herein, the four nominal species of erect bifoliate Microporella (M. bifoliata, M. hastigera, M. hyadesi and M. ordo) are revised, and one new Pliocene (M. tanyae sp. nov.) and three new Recent species (M. ordoides sp. nov., M. lingulata sp. nov. and M. modesta sp. nov.) are formally described. Furthermore, the lectotype and paralectotypes were designated for M. bifoliata and M. hastigera. An additional Recent species, Microporella sp. 1, is also described and illustrated but left in open nomenclature owing to the absence of ovicells in the single available fragment. Although the molecular phylogeny of Microporella has yet to be resolved, the diversity of character states present among the erect bifoliate species described here suggests that this colony growth-form is not monophyletic but has evolved on multiple occasions.